Kegiatan Pengembangan Minat dan Bakat pada Anak-anak dalam Kegiatan Keagamaan di Desa Lalang Kec. Tanjung Pura Kab. Langkat - Mahidin, Mahidin; Aulia, Mia; Hrp, Muhammad Royhan; Angi, Nur Fadila; Nurbaini, Nurbaini; Nuraida, Nuraida (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Every child has different potential, interests, and talents. A gifted child whose potential is optimized and well-stimulated can become one of the quality human resources that a country possesses, compared to a child who does not receive appropriate stimulation. Stimulation refers to various stimuli, such as play opportunities, learning facilities, or materials (such as stories or readings), which can trigger a child to learn or process teachings. Optimal is the highest condition in which someone or something can be done without damaging the existing elements. Potential is specific things that exist in a child, which appear more compared to their peers. Interest is a strong drive for someone to do everything they desire. Meanwhile, talent is a fundamental quality, skill, and disposition that is present from birth. Talent itself can be interpreted as a person's basic ability to learn in a relatively short time compared to others, yet the results are actually better. In short, this is the potential that someone has as a natural gift from birth. The purpose of the research is to optimize the potential, interests, and talents of children in Lalang Village for the future progress of human resources, to understand and provide solutions so that children in Lalang Village have space, direction, and a place to shape their character so that they can understand what potential they have and it is very important for their future. This research contains the reasons and processes for optimizing the potential, interests, and talents of children in Lalang Village.